Developing a Predictive Accreditation Simulator: A Strategic Quality Gateway for Private Universities in Indonesia - Bachri, Syaiful; Cahyadi, Eko Ruddy; Triyonggo, Yunus (Universitas Teuku Umar, 2025)
The accreditation landscape for private universities under the oversight of LLDIKTI Wilayah III in Indonesia is characterized by significant disparities in institutional readiness and compliance with national standards. Current data highlight a pressing need for strategic intervention, as a considerable proportion of institutions remain within the